Occurrence of self-reported enrollment with disabilities at the Universidade Federal do Pampa (Research, Society and Development, 2020)
The aim of this paper was the investigation about enrollment of self-reported students with disabilities (PWD) at the Universidade Federal do Pampa (UNIPAMPA) with the perspective of supporting future studies and inclusion policies. The methodology consisted of reflections from the data compilation to the selection process, from 2006 to 2018, they are obtained from the Pro-rectory of Graduation of UNIPAMPA and its websites. The results represent the occurrence of enrollments of self-declared enrollees PWD, in relation to the total number of enrollments in UNIPAMPA, for the period from 2006 to 2018, corresponds to 8.64%.In this context, it should be noted that in the period from 2011 to 2014, the self-reported enrollment PWD rate, in relation to the total number of enrollments was 7.40%. This event is attributed to affirmative action policies of UNIPAMPA, with quotas system for candidates with disabilities. It has started in 2015, there was a significant decrease in this index, where UNIPAMPA started to offer 3,120 total vacancies, with 2.02% of these vacancies to self-declared PWD according to the Term of Acceptance to the Student Selection System (SiSU). Considering the above, it is possible to conclude that national inclusive public policies gave access to higher education, including in UNIPAMPA. However, the challenges remain for public policies that regulate teacher education, development and didactic-pedagogical accompaniment of demands of teaching the subject matter.